1984
DOI: 10.1002/j.1460-2075.1984.tb02034.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence requirements for the accurate transcription of a protein-coding plastid gene in a plastid in vitro system from mustard (Sinapis alba L.)

Abstract: A nuclease‐treated plastid extract from mustard (Sinapis alba L.) allows efficient transcription of cloned plastid DNA templates. In this in vitro system, the major runoff transcript of the truncated gene for the 32 000 mol. wt. photosystem II protein was accurately initiated from a site close to or identical with the in vivo start site. By using plasmids with deletions in the 5′‐flanking region of this gene as templates, a DNA region required for efficient and selective initiation was detected ˜28‐35 nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 62 publications
1
75
1
1
Order By: Relevance
“…The mixtures were incubated for 20 min at 30 "C, transcripts prepared [26] and electrophoresed on 8% sequencing gels [56]. Total trichloroacetic-acid-precipitable material was determined as described [57].…”
Section: In Vitro Transcriptionmentioning
confidence: 99%
“…The mixtures were incubated for 20 min at 30 "C, transcripts prepared [26] and electrophoresed on 8% sequencing gels [56]. Total trichloroacetic-acid-precipitable material was determined as described [57].…”
Section: In Vitro Transcriptionmentioning
confidence: 99%
“…Studies of transcription in vitro using chloroplast RNA polymerase preparations from maize (Crossland et al, 1984;Bradley and Gatenby, 1985), mustard (Link, 1984), ' Current address: Cornell University, Plant Science Center, 139 Biotechnology Building, Ithaca, NY 14853.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that removal of the first two, generally very highly conseyved, nucleotides of the spinach tmM2 -35 sequence reduced transcription in vitro by a partially purified spinach chloroplast RNA polymerase by only 60% (Gruissem and Zurawski, 1985a), and a mustard chloroplast psbA gene construct without a -35 sequence (Link, 1984) was transcribed to some extent in vitro. Furthermore, tmR1 and tmS1 of spinach (Gruissem et al, 1986) are transcribed in vitro although they have no recognizable -1 O or -35 sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of multiple promoters of the rDNA cluster is unknown. A developmentally regulated promoter switching was hypothesized (37,41,42). In the attempt to isolate developmentally regulated genes in D.carota, we have cloned the chloroplast rDNA cluster.…”
Section: Discussionmentioning
confidence: 99%